If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 24 = -2 Reorder the terms: 24 + 11x = -2 Solving 24 + 11x = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 11x = -2 + -24 Combine like terms: 24 + -24 = 0 0 + 11x = -2 + -24 11x = -2 + -24 Combine like terms: -2 + -24 = -26 11x = -26 Divide each side by '11'. x = -2.363636364 Simplifying x = -2.363636364
| 8z+7=-5z-57 | | 8-n=-4+2(4-n) | | 5.25q-2(3q+1.25)=q+1 | | 4s+k=3r | | 9.2s=12.8s-3.96 | | 3y^2=72 | | -20p=-15.58-11.8p | | (9x-5)-(6x-8)= | | 2m+2n+2m+4n+8= | | 7x-5(5x+4)=142 | | 28M+16=4(4M-23) | | 7y^2-49y=0 | | -3=4x+6minusx | | 2n+8+2n+20= | | -n+25+6n+15=-12 | | 7x+5(5+4)=142 | | d(7-x)=4v | | 16+11v=2v-20+6v | | 10x-31+9x-13=127 | | R+300=-214 | | 152-x=138 | | 3(x+y)=8 | | 1.5(4w+1)=2.5w+1 | | -2n-(n-5)=n+1 | | 2x+4x-4=-2x+4 | | (y+2)(y-7)-1=(y+1)(y+3) | | 54=36+x | | -12-18q=-19q | | 14+4k=2+-2k | | 198=3x-5(6x+9) | | 35-6k=7(5-5k) | | 37=7-x |